Ultra-sensitive solution-processed broadband photodetectors based on vertical field-effect transistor. (17th December 2019) - Sulaman, Muhammad; Song, Yong; Yang, Shengyi; Li, Maoyuan; Saleem, Muhammad Imran; Chandraseakar, Perumal Veeramalai; Jiang, Yurong; Tang, Yi; Zou, Bingsuo
Abstract: In the past few decades, great attention has been paid to the development of IV–VI semiconductor colloidal quantum dots, such as PbSe, PbS and PbSSe, in infrared (IR) photodetectors due to their high photosensitivity, solution-processing and low cost fabrication. IR photodetectors based on field-effect transistors (FETs) showed high detectivity since the transconductance can magnify the drain–source current under certain applied gate voltages. However, traditional lateral FETs usually suffer from low photosensitivity and slow responsivity, which restricts their widespread commercial applications. In this work, therefore, novel vertical FET (VFET) based photodetectors are presented, in which the active layer is sandwiched between porous source electrode and planar drain electrode, resulting to ultrashort channel length. In this way, enhanced photoresponsivity and specific detectivity of 291 A W −1 and 1.84 × 10 14 Jones, respectively, can be obtained at low drain–source voltage ( V DS ) of −1 V and gate voltage ( V g ) of −2 V under 100 μ W cm −2 illumination intensity, which was better than that of the traditional lateral FET based photodetectors. Therefore, it is promising to fabricate broadband photodetectors with high performance and good stability by this easy approach.